2009
DOI: 10.1542/peds.2009-1255n
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Insurance on Satisfaction and Family-Centered Care for CSHCN

Abstract: BACKGROUND:Children with special health care needs (CSHCN) have worse health outcomes and satisfaction compared with children with typical needs. Although individual characteristics influence satisfaction and family-centered care, additional effects of health insurance and state child health policies are unknown. OBJECTIVES:To determine if satisfaction and family-centered care varied among CSHCN, after adjusting for individual characteristics, according to insurance type and state child health policies. METHOD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Public versus private insurance has been shown to be associated with less family-centered care in one study of children with special health care needs, 32 but another study found no association. 33 The public-private disparity in FCC found here has several potential explanations.…”
Section: Discussionmentioning
confidence: 99%
“…Public versus private insurance has been shown to be associated with less family-centered care in one study of children with special health care needs, 32 but another study found no association. 33 The public-private disparity in FCC found here has several potential explanations.…”
Section: Discussionmentioning
confidence: 99%
“…Covariates were identified as predisposing characteristics, enabling resources, or health care need factors according to previous FCC/SDM research (Bethell, Read, and Brockwood 2004;Denboba et al 2006;Thompson et al 2009;Coker, Rodriguez, and Flores 2010;Fiks et al 2010Fiks et al , 2012aGuerrero et al 2010;Kuo, Bird, and Tilford 2011;Kuo, Frick, and Minkovitz 2011;Raphael et al 2011;Romaire, Bell, and Grossman 2012a,b;Smalley et al 2014;Strickland et al 2014). Covariates used to characterize the study sample and controlled for in multivariable analysis included child age, sex, race/ethnicity, primary household language, household income relative to the federal poverty level (FPL), highest parent education level, census region, urbanness (i.e., metropolitan statistical region vs. nonmetropolitan statistical region), health insurance status and type, special health care needs status assessed by the CSHCN Screener (Bethell et al 2002a,b), illness/injury care need(s), specialty care need, and overall health status (Appendix SA2).…”
Section: Independent Variablesmentioning
confidence: 99%
“…The use of family expertise is essential to improving health care delivery [13]. However, only a few studies have engaged low-income, minority and/or non-English speaking families in this process to understand their perspective [14][15][16]. Some issues that families have previously identified were a lack of awareness of community resources, fragmented service lines, and provider organizations varying in their ability to meet linguistic and cultural needs of different individuals and families [17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%